Enhancing SMED: Changeover Out of Machine Evaluation Technique to implement the duplication strategy. Issue 4 (11th March 2016) - Braglia, M.; Frosolini, M.; Gallo, M.
Abstract: The present paper introduces an integrated approach to support the process engineers during the implementation of the conventional Single Minute Exchange of Dies. In particular, the proposed approach grounds on the new concept of 'duplication strategy', and takes advantage of an implementation tool here presented. It follows a top-down functional decomposition of machines, which helps practitioners identifying all those items impacting on the changeover process, and to propose appropriate intervention strategies. It aims at verifying the possibility of replicating entire parts of machines, fixtures and/or equipment, in order to externalise as many tasks as possible, yet carefully evaluating the cost-benefit ratio and any operational issue of the intervention. To show this novel approach, an actual implementation is hereby fully described. Finally, the results of the study are commented and proposals for future possible developments are suggested.